Inflammatory bowel and oxidative stress changes in an experimental model of portal hypertension: action of N-acetylcysteine - Licks, Francielli; Hartmann, Renata Minuzzo; Schemitt, Elizângela; Colares, Josieli Raskopf; Fillmann, Lúcio Sarubbi; Fillmann, Henrique; Marroni, Norma Possa (Journal of Coloproctology, 2016)
Introduction Portal hypertension (PH) is characterized by vasodilatation in the portal system and the bowel is one of the severely affected organs. N-acetylcysteine (NAC) is a molecule with important properties and widely used in clinical practice.Objective To evaluate NAC action in the bowel of animals submitted to the animal model of partial portal vein ligation (PPVL).Methods 18 male Wistar rats were divided into three experimental groups (n = 6): sham-operated (SO), PPVL, and PPVL + NAC. On the 8th day after surgery, N-acetylcysteine (10 mg/kg, ip) was administered daily for 7 days. On the 15th day the animals’ bowel was collected for oxidative stress analysis, immunohistochemistry and Western blot. We evaluated the expression of NF-KB and TNF-α by immunohistochemistry and of iNOS by Western blot. Lipid peroxidation was assessed by TBARS technique, and the activities of antioxidant enzymes superoxide dismutase (SOD) and glutation peroxidase (GPx) were checked.Results We observed an increased expression of NF-KB and TNF-α in PPVL group, and an increased iNOS expression assessed by Western blot. NAC reduced the expression of all proteins evaluated. We also observed an increase in oxidative stress in the bowel of mice PPVL group compared to controls (SO), and NAC was effective in reducing these values in PPVL + NAC group. Also, a reduction in the activity of SOD and GPx enzymes was observed in the diseased group, and NAC was able to restore the activity of the enzymes assessed.Conclusion We suggest the anti-inflammatory and antioxidant action of NAC in the bowel of animals submitted to PPVL model.
Keywords: N-acetylcysteine; Portal hypertension; Intestine; Oxidative stress; Inflammation